Medication Compliance of Patients Attending a Pain Clinic at a Tertiary Hospital in Malaysia - Kerpagam SR Nadarajan; Usha S. Rajah; T. Kumaravadivel Dharmalingam; Rajesh Kumar Muniandy (Penerbit UMS, 2023)
Pain is a public health problem with profound physical, emotional, and societal costs. Conventional oral analgaesics are usually the first treatment, which is cost-effective and relatively safe. However, medication noncompliance is a serious healthcare concern. Medication noncompliance has remained a significant challenge despite considerable efforts to improve patient compliance. Therefore, a study was done to assess medication compliance at a Pain Clinic in a tertiary hospital in Malaysia. The study period was from December 2019 to January 2020. A total of 180 patients participated in the study. The study showed that pain clinic patients’ medication compliance was 65%. With the improvement of medication compliance, the quality of life of patients with pain can be improved.